Access to general practice for people with intellectual disability in Australia: a systematic scoping review - Bradley Shea; Jodie Bailie; Sally Hall Dykgraaf; Nicola Fortune; Nicholas Lennox; Ross Bailie (BMC Primary Care, 2022)
Abstract Background People with intellectual disability experience inadequate access to general practice and poorer health outcomes than the general population. While some access barriers have been identified for this population, these studies have often used narrow definitions of access, which may not encompass the multiple dimensions that influence access to general practice. To address this gap, we conducted a scoping review to identify factors impacting access to general practice for people with intellectual disability in Australia, using a holistic framework of access conceptualised by Levesque and colleagues. Methods This scoping review followed Joanna Briggs Institute methodology and was guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews. Medline (Ovid), Scopus, CINAHL, Informit and PsycINFO databases were searched. Screening, full-text review and data extraction were completed by two independent reviewers, with consensus reached at each stage of the study. Data were extracted, coded and synthesised through deductive qualitative analysis – using the five corresponding conceptual dimensions within Levesque and colleagues’ theoretical framework of access, which incorporate both supply-side features of health systems and services, and demand-side characteristics of consumers and populations. Results The search identified 1364 publications. After duplicate removal, title and abstract screening and full-text review, 44 publications were included. Supply-side factors were more commonly reported than demand-side factors, with the following issues frequently identified as impacting access to general practice: limited general practitioner education about, and/or experience of, people with intellectual disability; communication difficulties; and inadequate continuity of care. Less frequently included were factors such as the health literacy levels, promotion of general practice services and availability of complete medical records. Conclusions This is the first scoping review to assess access barriers for people with intellectual disability using a comprehensive conceptualisation of access. The findings highlight the need for increased efforts to address demand-side dimensions of access to general practice and offer a basis for a balanced portfolio of strategies that can support recent policy initiatives to enhance access to care for people with intellectual disability.